ZnO-beta zeolite mediated simple and efficient method for the one-pot synthesis of quinoxaline derivatives at room temperature - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Central European Journal of Chemistry, 2010)
A rapid and an efficient one-pot method for the synthesis of quinoxalines catalysed by ZnO-beta zeolite at room temperature is described. This environmentally benign method provides several advantages over methods that are currently employed such as a simple work-up, mild reaction conditions, good to excellent yields, and a process to recover and reuse the catalyst for several cycles with consistent activity.
Keywords: cyclocondensation; Quinoxaline; Room temperature; ZnO-beta zeolite

Polyamides containing quinoxaline moiety - Patil, Vidyadhar B.; Sayyed, Maheboob M.; Mahanwar, Prakash A.; Wadgaonkar, Prakash P.; Maldar, Noormahamad N. (Journal of Polymer Research, 2011)
A new quinoxaline moiety containing aromatic diamine; 2,3-bis[4-(4-aminophenoxy)phenyl]quinoxaline (APQ) was synthesized starting from 4-methoxybenzaldehyde and was characterized by IR, (1)H, (13)C NMR and Mass spectrometry. Five new polyamides were synthesized by polycondensation of various aliphatic diacid / aromatic diacids namely, azelaic acid, bis(4-carboxyphenyl)dimethylsilane, 4,4'-oxybis(benzoicacid), isophthalic acid and terephthalic acid with APQ by Yamazaki's phosphorylation method using triphenyl phosphite as condensing agent. The polyamides were characterized by IR spectroscopy, solubility tests, inherent viscosity, X-ray diffraction technique, differential scanning colorimetry and thermogravimetric analysis. The polyamides had inherent viscosities in the range 0.39-0.45 dL/g in N, N-dimethylacetamide at 30 +/- 0.1 A degrees C. The polyamides were soluble in polar aprotic solvents such as N, N-dimethylacetamide, N, N-dimethylformamide, dimethylsulfoxide, N-methylpyrrolidone. X-Ray diffraction studies showed that polyamides were amorphous in nature. The polyamides showed glass transition temperatures in the range 104-205 A degrees C, according to differential scanning calorimetry. Thermogravimetric analysis exhibited initial decomposition temperatures above 348 A degrees C; indicating that these polyamides possessed excellent thermal stability.
Keywords: polyamides; Quinoxaline; solubility; Thermal properties; XRD

Efficient method for the synthesis of quinoxaline derivatives catalyzed by titanium silicate-1 - Chandrachood, Pranav S.; Jadhav, Amol R.; Garud, Dinesh R.; Deshpande, Nirmala R.; Puranik, Vedavati G.; Kashalkar, Rajashree V. (Research on Chemical Intermediates, 2020)
A series of quinoxaline derivatives were efficiently synthesized by convenient and simple procedure in excellent yields using 1 wt.% of titanium silicate (TS-1) catalyzed reaction of 1,2-diamines and 1,2-diketones in methanol at room temperature. This reaction is scalable to multigram scale and the catalyst is recyclable. [GRAPHICS] .
Keywords: 2-Diketones; Aromatic 1; o-Phenylenediamine; Quinoxaline; Room temperature; Titanium silicate-1

CoBr2-catalyzed straightforward synthesis of quinoxalines via dehydrogenative coupling strategy - Dubey, Shivansh; Punji, Benudhar (Chemistry-an Asian Journal, 2025)
Establishing a benign and straightforward protocol for synthesizing biorelevant and synthetically valuable quinoxaline is very important. Herein, we report a simple and efficient protocol for the sustainable synthesis of diverse quinoxaline derivatives catalyzed by cobalt salt. The reaction proceeds through the dehydrogenative coupling of alkyl and aryl ethane 1,2-diols with aryl diamines in the presence of a catalytic CoBr2/K2CO3. The usage of the greener solvent 2-MeTHF and the release of H2 and H2O as the sole byproducts make the process advantageous. The protocol led to the synthesis of diverse quinoxalines bearing synthetically useful functionalities, such as fluoro, chloro, bromo, cyano, trifluoromethyl, and ether. The reaction is presumed to proceed via the dehydrogenative-condensation pathway involving a cobalt-hydride intermediate.
Keywords: cobalt; dehydrogenative coupling; heterocycles; ligand-free process; Quinoxaline